Effectiveness of Village Government Financial Accounting System in Supporting Good Governance - Setriani, Eva Nur; Kusmilawaty, Kusmilawaty; Nasution, Yenni Samri Juliati (Journal La Bisecoman, 2024)
This study aims to analyze the effectiveness of the village government's financial accounting system in supporting good governance in Aek Korsik Village, Aek Ledong District. This study uses a qualitative method with a case study approach. Data collection techniques are carried out through interviews and observations. Data analysis techniques using the Miles and Huberman model include the data reduction stage, the data presentation stage, and the conclusion drawing or verification stage. The results of the study show that the implementation of the Village Financial System Application (SISKEUDES) in Aek Korsik Village has been running well and effectively in supporting financial governance (Good Governance). However, in the process there are obstacles faced, namely the system sometimes does not support and errors. In addition to these obstacles, the quality of the Village Government's human resources and the lack of supervision from the government resulted in the Village Government being less thorough and responsive so that the services of the Aek Korsik village government were not good in presenting information.